Clementina Black at the TUC, 1888 (1888)
1888 1880-1914 "Clementina Black at the TUC, 1888" [EP0052b], 1888 In 1888, Clementina Black moved the first TUC equal pay resolution. However, she had problems in gaining admission as a delegate. This report comes from the 15 September, 1888 issue of The Women's Union Journal published by the Women's Trade Union League.